Dmitrichenko N.F., Priymak L.B., Dovgal A.G., Bilyakovich O.N., Savchuk A.N., Turitsya Y.A. Selec-tion of the sublayer content for the thermal barrier coating heat affected components of aircraft ground support equipment. - Дмитриченко, М.Ф.; Приймак, Л.Б.; Довгаль, А.Г.; Білякович, О.М.; Савчук, А.М.; Туриця, Ю.О. (Problems of Tribology, 2017)
Adhesive behavior of components composite Al2O3–ZrO2 when wetting in vacuum by the Ni-Al components melt have been researched, in order to investigate the possibility of this alloys application as an intermediate layer for the steel elements of aircraft ground support equipment, and high temperature behavior of this melts on border of the system “ceramics-melt”. It has been established, that the melts of pure nickel does not wet the Al2O3–ZrO2 components ceramics, however admixtures of the aluminium in nickel in rate of 15% substantially intensify the process of adhesive interaction forming the contact angles θ = 20°. Main figures of adhesive interaction have been calculated and the structure of contact area has been researched. Application advisability of specified alloy Ni-15 % Al for the intermediate layer of the coating system Al2O3–ZrO2 for protection of steel heat-bearing elements of aircraft ground support equipment has been detected. Key words: aviation ground technology, heat-protective coating, adhesion properties, ceramic sample.